Kolok.id: An Aplication for Digital Learning Media Integrated with Game and Kolok Dictionary to Improve Kolok Students’ Learning Performance in Covid-19 Pandemic - Ni Putu Ayu Pirdayanti; Ni Ketut Anggriani; Gusti Aditya Trisna Murti; I Ketut Andika Pradnyana; I Wayan Pardi (Universitas Pendidikan Ganesha, 2024)
SD Negeri 2 Bengkala is an inclusive school that aims to improve the quality of education for kolok students. Kolok means dumb and deaf. Problems faced by Kolok students in learning activities namely 1) as they have physical limitations to be unable to speak and hear something, this situation hardly affects their learning process, 2) teachers have not used creative and innovative learning media, 3) Kolok students find difficulties to understand abstract material, moreover when they have nobody as their assistant (kolok translator) to help them understand their lesson. Knowing this situation, Kolok.id is developed to overcome problems encountered by most of kolok students. Kolok.id is an application developed to help kolok students receive lesson easier and facilitate their communication needs. The main features contained in the kolok.id application includes basic competencies and indicators, teaching materials, crossword puzzle games, quizzes, kolok dictionaries, and guide book. Kolok.id application is also relevant to use during the Covid19 pandemic to support Kolok students learning from home. In addition, this application can also be used anytime and anywhere. The development of Kolok.id application uses the method of Multimedia Development Life Cycle (MDLC) which consists of 6 development stages, namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Kolok.id application has gone through the testing stages of beta and alpha with very good results.